2016
DOI: 10.1093/mmy/myw129
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the risk of false positive serum galactomannan among patients receiving piperacillin/tazobactam for febrile neutropenia

Abstract: Galactomannan (GM) assay is commonly used as an early diagnostic tool for invasive fungal infection (IFI) in high-risk hematology patients. False positivity is frequently observed in GM with the use of piperacillin/tazobactam. The usage of generic drugs over the original brand has a significant cost advantage. The aim of this study was to assess the performance of GM test among patients receiving original and generic piperacillin/tazobactam formulations. The study included 85 adult patients; 62.4% were male wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Aspergillus antigens are an important biomarker for the early diagnosis of invasive aspergillosis (IA) [42]. In their landmark study of 1979, Reiss and Lehmann [43] found that galactomannan (GM) antigen, a polysaccharide present in the cell wall of most Aspergillus species, is released from growing hyphae during infection.…”
Section: Aspergillosismentioning
confidence: 99%
“…Aspergillus antigens are an important biomarker for the early diagnosis of invasive aspergillosis (IA) [42]. In their landmark study of 1979, Reiss and Lehmann [43] found that galactomannan (GM) antigen, a polysaccharide present in the cell wall of most Aspergillus species, is released from growing hyphae during infection.…”
Section: Aspergillosismentioning
confidence: 99%
“…The detection of galactomannans in serum and/or BAL of patients admitted during the case period (2,75%) and the control period (5,03%) did not show any statistically significant correlation between the presence of the renovation activities compared to the absence of these. The GM test is the most rapid detection method for IA diagnosis; nevertheless, false positive could be observed in patients simultaneously treated with piperacillin/tazobactam generic formula 33. Our study shows that for 2 patients the positivity to GM test was not confirmed by clinical and radiological data suggesting an alleged interference between antimicrobial agent and the GM detection assay.…”
Section: Discussionmentioning
confidence: 55%
“…False positive GM antigenemia has been described before and was associated with the administration of generic piperacillin/tazobactam [18][19][20][21][22], hypercaloric drinks [23], antifungal prophylaxis [24,25], and even ice-pop ingestion and pasta. In most cases, the proposed mechanism for false positivity was the contamination of the product with GM.…”
Section: Discussionmentioning
confidence: 99%